Ethanolic Extract of Pluchea indica Less leaf Increases Serum Growth Hormone in Lactating Rats - Rul Afiyah Syarif; Nungki Anggorowati; Mia Munawaroh; Mae Sri Hartati Wahyuningsih (Majalah Obat Tradisional, 2021)
The objectives of the study were to evaluate the effect of ethanolic extract of P. indica Less leaf (EPI) on serum growth hormone (GH), milk yield, body weight gain of dams, and dam’s organ weight in lactating rats. A total of 25 lactating rats with six pups were randomized and distributed to one of five treatments (control (RO water), standard (domperidone 2,5 mg/kg BW/day), EPI 250 (250 mg/kg BW of EPI), EPI 500 (500 mg/kg BW of EPI), and EPI 750 (750 mg/kg BW of EPI)). The treatment was administered daily starting from the 2nd until the 15th day of lactation. On the 16th day serum growth hormone level, body and organ weight of rats were measured. Serum GH levels in the EPI 750 group (1963.25 ± 360.91 pg/µL) increased significantly compared to the domperidone (409.46 ± 28.80 pg/µL) and the control group (723.40 ± 95.78 pg/µL, p0.05). There was significant body weight gain in the EPI 750 group compared with the domperidone group. There was no significant difference in organ weight gain in each group. The study revealed that ethanolic extract of P. indica Less leaf can increase serum growth hormone in lactating rats.